Qualification, socialisation and/or subjectification – three international organisations' prioritisation of the purposes of adult education and learning from the 1970s to the 2010s. Issue 1 (2nd January 2022) - Larson, Anne; Cort, Pia
ABSTRACT: This article examines the purposes UNESCO, OECD and EU historically have attributed to adult education and learning. The aim is to explore changes in international adult education and learning policies from the 1970s until the present day and outline how different international organisations have pushed for specific conceptualisations of what 'adult education and learning is good for'. The analysis draws on Biesta's domains of educational purpose to demonstrate how the functions of adult education and learning have changed as the welfare state has transformed into a neoliberal competition state. Based on an analysis of key policy documents, the article shows how each of the organisations has sought to set an agenda in line with its founding visions. UNESCO pushing for an agenda centred on su bjectification and the aim of empowering the individual, but also including strong elements of both qualification and socialisation. OECD, on the other hand, having a more narrow understanding, seeing the purpose of adult education and learning as qualification for the labour market as part of a growth ideology. Finally, EU pushing both socialisation of European citizens and labour market qualifications. The analysis shows how, over the decades, adult education and learning policy has narrowed to focus on a primarily instrumental purpose, which creates new attributed meaning for both the purpose of socialisation and subjectification.